(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
To assess the effects of metformin and glibenclamide each one alone on complete blood picture (CBP) in type 2 diabetic patients. A case control study. This study was conducted during the period from 1/5/2011 to 31/1/2012 in Ibn Sina hospital in Mosul city. CBP were measured in patients suffering from type 2 diabetes mellitus. Group 1: 21 patients on metformin therapy (850-1500mg/day), group 2: 23 patients on glibenclamide therapy (5-10mg/day), also 22 apparently healthy volunteers were taken as the control group. Blood samples were taken from the three groups and analyzed for full blood count including red blood cells count (RBCs) ,white blood cell count (WBCs), and platelet count, hemoglobin (Hb) , mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and hematocrit (PCV). WBC count was higher in group 2 than that in group 1 and control group. The other parameters of complete blood picture in group 1 and 2 showed no significant differences compared with the control group. Metformin and glibenclamide have no significant effect on CBP except for the effect metformin which decreases WBC and platelet level which are already elevated in type 2 DM , but remain within the normal range. Such effect could not be seen in glibenclamide group